The re-organization of the main islamic communities in Turkey, in the post 1980 coup era - Bilgili, Alper. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2006., 2006)
This thesis aims to provide a preliminary investigation and evaluation of themain Islamic Communities̕ (namely Nurcu, Süleymancı and İskenderpasa Communities) re-organization during the post 1980 coup era. This thesis argues that these Islamist Communities became more active in this period in the political andsocio-economic spheres. Thus, the tendency to link the current political andeconomic structures of these communities to their early organizations will bequestioned. While doing this, their organizations before the coup, during the coupadministration, and in the Özal era are going to be analyzed, in chronological order. The organization in this thesis includes these Communities̕ activities in the political,economic and media spheres. Their re-organizations in the post coup era, in thesefields will be analyzed comparatively. Hence, this thesis further aims to find out the possible relations between this increasing level of activities of the Communities andthe political and economic policies of the governments. These aims will be realized through the investigation of the State and Military reports on these Communities, the secondary sources written on them, a close reading of these communities̕ own journals and Newspapers and an investigation oftheir economic institutions.|KEYWORDS: Naqshibandis, Nurcu Community, Suleymancı Community, Iskenderpasa Community, Policies of the Özal era .
Keywords: Turkey -- Politics and government -- 1980-; Nurculuk.; Süleymancılık.